The Effect of Excellent Service, Transformational Leadership, and Career Development on Patient Satisfaction at Hospitals in West Java - Muhamad Ammar Muhtadi; Sigit Prasety; Weda Febriyanto (Westscience Press, 2024)
This study investigates the impact of excellent service, transformational leadership, and career development on patient satisfaction in hospitals across West Java. Employing a quantitative approach, the research involved a sample of 160 patients and utilized a Likert scale ranging from 1 to 5 for data collection. Structural Equation Modeling-Partial Least Squares (SEM-PLS 3) was applied for data analysis. The findings reveal that all examined hypotheses are positive and significant, indicating that high-quality service, effective transformational leadership, and robust career development programs contribute significantly to enhancing patient satisfaction. Career development emerged as the most influential factor, followed by transformational leadership and excellent service. These results underscore the importance of these factors in hospital management and suggest strategies for healthcare facilities to improve patient experiences and outcomes. The study provides valuable insights for hospital administrators and policymakers aiming to elevate patient satisfaction levels in West Java.